Designing Systematic Conservation Assessments that Promote Effective Implementation: Best Practice from South Africa - ANDREW T. KNIGHT; AMANDA DRIVER; RICHARD M. COWLING; KRISTAL MAZE; PHILIP G. DESMET; AMANDA T. LOMBARD; MATHIEU ROUGET; MARK A. BOTHA; ANDRE F. BOSHOFF; J. GUY CASTLEY; PETER S. GOODMAN; KATHY MACKINNON; et al. (Conservation Biology, 2006)
Systematic conservation assessment and conservation planning are two distinct fields of conservation science often confused as one and the same. Systematic conservation assessment is the technical, often computer‐based, identification of priority areas for conservation. Conservation planning is composed of a systematic conservation assessment coupled with processes for development of an implementation strategy and stakeholder collaboration. The peer‐reviewed conservation biology literature abounds with studies analyzing the performance of assessments (e.g., area‐selection techniques). This information alone, however, can never deliver effective conservation action; it informs conservation planning. Examples of how to translate systematic assessment outputs into knowledge and then use them for “doing” conservation are rare. South Africa has received generous international and domestic funding for regional conservation planning since the mid‐1990s. We reviewed eight South African conservation planning processes and identified key ingredients of best practice for undertaking systematic conservation assessments in a way that facilitates implementing conservation action. These key ingredients include the design of conservation planning processes, skills for conservation assessment teams, collaboration with stakeholders, and interpretation and mainstreaming of products (e.g., maps) for stakeholders. Social learning institutions are critical to the successful operationalization of assessments within broader conservation planning processes and should include not only conservation planners but also diverse interest groups, including rural landowners, politicians, and government employees.